The Mission of Paul in Macedonia: The Proclamation of the Gospel as an Anti$imperial Message - Solokha, Sergey (Bogoslovskie razmyšlenija, 2011)
"The Mission of St. Paul in Macedonia" examines the essence of the opposition faced by the Apostle Paul when he brought the good news to Europe. Paul was accused that his apostolic international mission was anti-traditional, anti-cultural, and illegal. His main accusers were businessmen in the city of Philippi and the Jews of Thessalonica, who used political power and mobs against the Gospel. The Apostle preached in towns with well-developed Emperor cults during the reign of Claudius, who had already expelled the Jews from Rome on the basis of religion. Although the Gospel had political implications in its key terms and conflicted with the royal theology of Caesar, this was not the main reason for persecution on the part of the authorities. Paul sees the main opponent of the Gospel as neither the Emperor who resides in Rome, nor the Jews, the religious zealots, but as Satan, who uses the authorities as instruments of opposition.